Positive electrode lithium supplementing material and preparation method and application thereof

By using manganese-based compounds and performing non-stoichiometric ratio control and doping treatment, the existing problems of high cost and poor stability of positive electrode lithium supplement materials are solved, and a positive electrode lithium supplement material with low activation voltage and high interface stability is achieved. Industrial application.

CN119404333APending Publication Date: 2025-02-07NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202480002667.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing positive electrode lithium supplement materials such as lithium ferrate and lithium nitride have problems such as high raw material costs, poor interface stability and unstable air, making them difficult to store and industrially apply.

Method used

Manganese-based compounds are used as the positive electrode lithium supplement material, and defect-rich materials are formed by controlling the heterovalent isoforms of doped elements through non-stoichiometric ratios, reducing activation difficulty and improving interface stability.

Benefits of technology

It achieves a low activation voltage, excellent interface stability and low cost positive electrode lithium supplement material, suitable for industrial applications and can remain active when placed in the air for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404333A_ABST
    Figure CN119404333A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode lithium supplementing material and a preparation method and application thereof. The positive electrode lithium supplementing material is a non-stoichiometric ratio compound, the chemical composition of the positive electrode lithium supplementing material is Li (2-x) Mn (1-y) MyO3, M is a doping element, x is more than 0 and less than or equal to 0.2, and y is more than or equal to 0 and less than or equal to 0.2; the valence state of M is not + 4, or the pure-phase lithium oxide of M and the layered Li2MnO3 material are isomerized. The positive electrode lithium supplementing material has a good lithium supplementing effect, and also has relatively low activation difficulty and excellent interface stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a lithium supplement material, and in particular to a positive electrode lithium supplement material and a preparation method and application thereof, belonging to the technical field of lithium ion batteries. Background Art

[0002] Lithium replenishment technology for lithium-ion batteries is an important means to improve battery energy density. During the first charging process of lithium-ion batteries, the organic electrolyte will undergo redox decomposition at the electrode interface to form a solid electrolyte membrane, consuming a large amount of active lithium, resulting in low coulomb efficiency in the first cycle of the battery, reducing the capacity and energy density of the lithium-ion battery. In addition, redox decomposition at the electrode interface will continue to occur during the cycle, continuously consuming active lithium, resulting in a continuous decrease in battery capacity and energy density.

[0003] Lithium replenishment technology is a technology that replenishes lithium-ion batteries with additional active lithium to offset the energy density decay caused by the consumption of active lithium. Currently, lithium replenishment technology can be divided into two categories: positive electrode replenishment and negative electrode replenishment. Among them, negative electrode replenishment mainly includes the following methods: (1) negative electrode chemical replenishment. The material used for lithium insertion is generally a hexane solution of n-butyl lithium or an acetonitrile solution of potassium iodide. The lithiation agent used in chemical lithium replenishment technology is generally toxic and dangerous; (2) negative electrode lithium metal self-discharge replenishment. Lithium sheets or lithium powder are directly pressed on the negative electrode. This method is difficult to process and has certain dangers due to the high activity of lithium metal; (3) negative electrode electrochemical replenishment. By introducing metallic lithium and the negative electrode to form a counter electrode, the electrochemical charge and discharge depth is controlled to achieve pre-lithiation of the negative electrode sheet. This method has the most complex process operation and is not easy to use for mass production. In summary, negative electrode replenishment is difficult and dangerous, and it is difficult to apply industrially. Positive electrode replenishment is a technology that adds compounds that are easily delithiated under high voltage to the positive electrode and uses the high voltage of the formation charging process to replenish active lithium to the battery cell. Since most positive electrode lithium supplements are safe to use, they are widely used in the industry.

[0004] However, currently commonly used lithium supplements such as lithium ferrite and lithium nickel oxide have problems with high raw material costs and poor interface stability. They are unstable in the air, and exposure to air will cause rapid capacity decay or even failure, making them difficult to store. Summary of the invention

[0005] The present application provides a positive electrode lithium replenishing material, which has a good lithium replenishing effect, a low activation voltage and excellent interface stability.

[0006] The present application also provides a method for preparing a positive electrode lithium replenishing material, which can obtain the above-mentioned positive electrode lithium replenishing material with good lithium replenishing effect, low activation voltage and excellent interface stability by mixing and sintering a lithium source, a manganese source and a compound of a doping element M in a specific designed ratio.

[0007] The present application also provides a positive electrode sheet, comprising the above-mentioned positive electrode lithium replenishing material, and the positive electrode sheet has the advantages of strong stability and good lithium replenishing effect.

[0008] The present application also provides a lithium-ion battery, comprising the above-mentioned positive electrode sheet, and the battery has excellent first-cycle coulomb efficiency and cycle capacity retention rate.

[0009] The first aspect of the present application provides a positive electrode lithium supplement material, the positive electrode lithium supplement material is a non-stoichiometric compound, and the chemical composition of the positive electrode lithium supplement material is Li2- x Mn 1-y M y O3, where M is a doping element, 0<x≤0.2, 0≤y≤0.2;

[0010] The valence state of M is not +4, or the pure phase lithium oxide of M is isomerized with the layered Li2MnO3 material.

[0011] The positive electrode lithium supplement material as described above, wherein M includes one or more of Mg, Al, Ti, V, Cr, Fe, Co, Ni, Zn, Sr, Y, Zr, Nb, Mo, and W.

[0012] The positive electrode lithium replenishing material as described above, wherein the positive electrode lithium replenishing material is a primary particle.

[0013] The positive electrode lithium supplement material as described above, wherein the D50 particle size of the positive electrode lithium supplement material is 0.1 μm to 2 μm.

[0014] The positive electrode lithium supplement material as described above, wherein the specific surface area of ​​the positive electrode lithium supplement material is 0.5 m 2 / g~24m 2 / g.

[0015] The second aspect of the present application provides a method for preparing the positive electrode lithium supplement material as described above, wherein the preparation method comprises the following steps:

[0016] 1) mixing a manganese source, a lithium source and a compound containing a doping element M according to a designed ratio to obtain a mixture;

[0017] 2) Sintering the mixed material to obtain the positive electrode lithium supplement material.

[0018] The preparation method as described above, wherein the mixing treatment is carried out under solid phase conditions.

[0019] The preparation method as described above, wherein the sintering process comprises a primary sintering and a secondary sintering performed sequentially;

[0020] The primary sintering temperature is 450-600°C and the sintering time is 4-8h;

[0021] The secondary sintering temperature is 750-950° C., and the sintering time is 6-12 hours.

[0022] The third aspect of the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode lithium supplement material provided in the first aspect of the present application.

[0023] A fourth aspect of the present application provides a lithium-ion battery, comprising the positive electrode sheet provided in the third aspect of the present application.

[0024] The implementation of this application has at least the following advantages:

[0025] Compared with traditional positive electrode lithium supplement materials such as lithium ferrite and lithium nickelate, the positive electrode lithium supplement material provided by the present application is a manganese-based compound, which has ultra-high interface stability, can remain active after being placed in the air for a long time, is easy to store, and the present application makes the positive electrode lithium supplement material rich in defects by performing non-stoichiometric ratios and optional aisovalent isomerization doping on the composition of the positive electrode lithium supplement material, thereby reducing the difficulty of activation of the manganese-based lithium supplement material, and matching the activation voltage with the operating voltage of conventional high-voltage batteries. In addition, manganese ore is abundant in nature, and its raw material cost is much less than that of lithium supplement materials such as lithium ferrite and lithium nickelate. Therefore, the positive electrode lithium supplement material of the present application has a good lithium supplement effect while also having a lower cost, a smaller activation difficulty and excellent interface stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the XRD pattern of Li2MnO3 pure phase material;

[0027] Figure 2 This is the XRD pattern of LiCoO2 pure phase material;

[0028] Figure 3 This is the SEM image of the positive electrode lithium replenishing material of Example 1. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in combination with the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0030] The first aspect of the present application provides a positive electrode lithium supplement material, which is a non-stoichiometric compound, and its chemical composition is Li2- x Mn 1-y M y O3, where M is a doping element, 0<x≤0.2, 0≤y≤0.2;

[0031] The valence state of M is not +4, or the pure phase lithium oxide of M is isomerized with the layered Li2MnO3 material.

[0032] Compared with traditional positive electrode lithium supplement materials such as lithium ferrite and lithium nickelate, the positive electrode lithium supplement material provided by this application is a manganese-based compound, which has ultra-high interface stability and can remain active after being placed in the air for a long time. In addition, manganese ore is abundant in nature, and its raw material cost is much lower than that of lithium supplement materials such as lithium ferrite and lithium nickelate. However, the conventional manganese-based lithium supplement material is too stable and needs to be activated at a high voltage of >5.5V. Even at high voltage, the activation efficiency is still not high, which does not match the operating voltage range of conventional high-voltage batteries. This application greatly reduces the difficulty of activating manganese-based lithium supplement materials by controlling defects in the composition of the positive electrode lithium supplement material, so that it can be activated within a voltage not higher than 4.8V, and has good matching with the operating voltage of conventional high-voltage batteries.

[0033] The defect control of the composition of the positive electrode lithium supplement material in the present application is embodied in two aspects: non-stoichiometric ratio control and optional doping control.

[0034] Non-stoichiometric ratio control refers to the fact that the positive electrode lithium supplement material of the present application is a non-stoichiometric compound. Non-stoichiometric ratio refers to the chemical formula Li 2-x Mn 1-y M y The sum of the positive valences of the cations in O3 is not equal to the sum of the negative valences of the anions. For example, when y is 0, the chemical composition that satisfies the stoichiometric ratio should be Li2MnO3. However, this application limits the subscript of Li to 2-x, and x>0, so that its composition does not satisfy the stoichiometric ratio, thereby generating certain lithium vacancies and reducing the difficulty of activating the positive electrode lithium supplement material.

[0035] Doping control means that the element M doped in the positive electrode material of the present application is heterovalent with the matrix Mn element, or the pure phase lithium oxide of the element M is isomeric with the layered Li2MnO3 material, wherein heterovalent means: the valence of the element M is different from that of the Mn element, that is, the valence of the element M is not +4, and isomeric means: the lithium oxide of the element M does not belong to the layered structure with the space group of C2 / m, and the space group of the material structure can be indexed by XRD testing and spectrum peak indexing. Taking the element M as Co as an example, Figure 1 This is the XRD pattern of Li2MnO3 pure phase material. Figure 2XRD pattern of pure-phase LiCoO2 material. Through indexing of spectral peaks, it can be known that Figure 1 and Figure 2 retrieval shows that Li2MnO3 belongs to the C2 / m space group, and LiCoO2 belongs to the R-3m space group. The typical difference between the two is that materials with the C2 / m space group structure will show superlattice peaks at 20-35° under the test conditions of a Cu target. Thus, it can be verified that the pure-phase lithium cobalt oxide of Co element is isomeric with the layered Li2MnO3 material.

[0036] Doping control can form a local multi-phase structure in the material, reduce the crystal domain size of the Li2MnO3 structure, and play a role similar to grain refinement. In addition, the locally formed multi-phase crystals have more grain boundaries, which is beneficial to lithium ion conduction, thereby reducing the activation difficulty of the cathode lithium supplement material.

[0037] In this application, by controlling x to satisfy 0 < x ≤ 0.2, while constructing non-stoichiometric defects to reduce the activation difficulty, the material itself also has sufficient lithium elements to achieve a good lithium supplement effect. By controlling y to satisfy 0 ≤ y ≤ 0.2, while constructing doping defects to reduce the activation difficulty, the material itself also has sufficient manganese elements to maintain excellent stability.

[0038] In summary, the cathode lithium supplement material provided by this application has a good lithium supplement effect, and at the same time has a low cost, a small activation difficulty, and excellent interfacial stability, which is convenient for storage and industrial application.

[0039] In a preferred embodiment, M includes one or more of Mg, Al, Ti, V, Cr, Fe, Co, Ni, Zn, Sr, Y, Zr, Nb, Mo, W. These elements are not only beneficial to constructing defects to reduce the activation difficulty of the cathode lithium supplement material, but also have good compatibility with the bulk Li2MnO3 material, which is beneficial to uniform doping and is not easy to precipitate or form segregated compounds.

[0040] In a preferred embodiment, the cathode lithium supplement material of this application is primary particles. Compared with secondary particles, primary particles can exhibit a higher irreversible capacity and better lithium supplementation.

[0041] In a preferred embodiment, the D50 particle size of the cathode lithium supplement material of this application is 0.1 μm to 2 μm, specifically it can be 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, 0.9 μm, 1.1 μm, 1.3 μm, 1.5 μm, 1.7 μm, 2 μm or the range value composed of any two of the above values. When the D50 particle size of the cathode lithium supplement material is less than 0.1 μm, the contact area with the electrolyte is too large, which is likely to cause gas generation due to decomposition; when the D50 particle size of the cathode lithium supplement material is greater than 2 μm, it is not conducive to the exertion of the lithium supplement capacity.

[0042] The specific surface area (BET) of the positive electrode lithium supplement material is also a key factor affecting battery performance. The larger the specific surface area, the more conducive it is to the activation of the lithium supplement material and the utilization of its capacity. However, an excessively large specific surface area will cause the lithium supplement material to react with the electrolyte to produce gas, which is detrimental to the battery's cycle performance. Based on the above considerations, it is preferred that the specific surface area of ​​the positive electrode lithium supplement material be controlled to 0.5 m 2 / g~24m 2 / g, specifically 0.5m 2 / g, 1.0m 2 / g, 3.0m 2 / g, 5.0m 2 / g, 8.0m 2 / g, 10.0m 2 / g, 13.0m 2 / g, 16.0m 2 / g, 19.0m 2 / g, 21.0m 2 / g, 24.0m 2 / g or a range consisting of any two of the above values.

[0043] The second aspect of the present application provides a method for preparing a positive electrode lithium supplement material, wherein the preparation method comprises the following steps:

[0044] 1) mixing a manganese source, a lithium source and a compound containing a doping element M according to a designed ratio to obtain a mixture;

[0045] 2) Sintering the mixed material to obtain a positive electrode lithium supplement material.

[0046] In step 1), the design ratio refers to the molar ratio between the raw materials so that the chemical composition of the final positive electrode lithium supplement material meets the Li 2-x Mn 1-y M y The composition of O3 is limited, wherein 0<x≤0.2, 0≤y≤0.2.

[0047] The chemical composition of the positive electrode lithium supplement material is Li 1.95 Mn 0.9 Co 0.1 Taking O3 as an example, where the doping element M is Co, the molar ratio of the manganese source, the lithium source and the compound containing the doping element Co should satisfy the molar ratio of the Li element in the lithium source, the Mn element in the manganese source and the Co element in the compound containing the doping element Co of 1.95:0.9:0.1.

[0048] The present application does not specifically limit the types of manganese sources, lithium sources and compounds containing doping elements M, and they can all be selected from manganese sources, lithium sources and compounds containing doping elements M conventionally used in lithium-ion batteries. Specifically, the manganese source includes one or more of manganese monoxide (MnO), manganese dioxide (MnO2), manganese trioxide (Mn2O3), manganese tetraoxide (Mn3O4), manganese oxalate (MnC2O4) and hydrates of the above compounds; the lithium source includes one or more of lithium hydroxide (LiOH), lithium carbonate (Li2CO3) and hydrates of the above compounds; the compound containing doping element M includes one or more of oxides, hydroxides, chlorides, sulfates, nitrates, acetates and carbonates of element M.

[0049] In step 1), the mixing treatment is preferably carried out under solid phase conditions, and the solid phase conditions mixing refers to directly mixing the solid particles of the manganese source, the lithium source and the compound containing the doping element M without adding a solvent. Sintering after mixing under solid phase conditions is not only conducive to obtaining a positive electrode lithium supplement material with a primary particle morphology, but also conducive to large-scale industrial production of tons of positive electrode lithium supplement materials.

[0050] The sintering treatment in step 2) can be carried out under conventional conditions in the art, and can be carried out in an air atmosphere or an oxygen atmosphere.

[0051] In a preferred embodiment, the sintering process includes primary sintering and secondary sintering performed sequentially; wherein the primary sintering temperature is 450-600°C, and the sintering time is 4-8 hours; the secondary sintering temperature is 750-950°C, and the sintering time is 6-12 hours.

[0052] The first sintering is carried out at a lower temperature, which is more conducive to the formation of material defects. The second sintering is carried out at a higher temperature, which is conducive to removing the bound water on the surface of the material and the moisture inside the material, avoiding swelling during the use of the battery.

[0053] If the heating rate or cooling rate is too fast, it will easily cause deformation of the material, thus affecting the quality of the product; if the heating rate or cooling rate is too slow, it will lead to too long processing time, thus increasing production costs. Based on the above considerations, the heating rate during sintering is controlled to be 2-10℃ / min, and the cooling rate is controlled to be 2-5℃ / min.

[0054] In addition, ball milling can be introduced before the primary sintering and the secondary sintering. Ball milling can make the raw materials of the primary sintering and the raw materials of the secondary sintering more fully mixed, and is conducive to obtaining a positive electrode lithium supplement material with more uniform powder distribution and better consistency.

[0055] In a specific embodiment, the ball milling treatment before the primary sintering includes: using a ball mill to mix the mixed material at a rotation speed of 300-600 rpm for 2-6 hours; the ball milling treatment before the secondary sintering includes: using a ball mill to mix the primary sintering material at a rotation speed of 600-1200 rpm for 2-6 hours.

[0056] In order to obtain a positive electrode lithium supplement material of a designed size, after the sintering process is completed, the sintered material is also crushed. In a specific embodiment, the crushing process includes: using a ball mill at a rotation speed of 300 to 800 rpm to the designed size.

[0057] Furthermore, after the crushing process, the crushed material can be washed, dried or re-fired to remove the residual alkali and moisture on the surface. The re-firing temperature can be controlled to 180°C to 350°C, and the time can be controlled to 2 to 6 hours. After washing and drying, the residual alkali on the surface of the positive electrode lithium supplement material satisfies: Li2CO3≤3.5wt%, LiOH≤1.2wt%. Within the above residual alkali content range, the appearance of gel-like substances in the positive electrode lithium supplement material during the slurry formation process can be avoided.

[0058] Furthermore, after washing and drying, a demagnetization process is also included. The demagnetization can be carried out by conventional operations in the art, as long as the content of magnetic substances in the material is less than 50 ppb.

[0059] In addition, in order to obtain positive electrode lithium supplement materials with high size consistency, the sintered or ball-milled materials can be sieved, preferably using a 300-mesh sieve.

[0060] The third aspect of the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode lithium supplement material provided in the second aspect of the present application.

[0061] The present application does not impose any particular limitation on the positive electrode current collector, and a current collector conventionally used in the art, such as aluminum foil, can be used, which can be obtained commercially.

[0062] In addition to the above-mentioned positive electrode lithium supplement material, the positive electrode active material layer of the present application also includes components such as positive electrode active material, conductive agent, binder, etc. Among them, the positive electrode active material, conductive agent and binder can be selected from materials conventionally used in the field. Specifically, the positive electrode active material can be selected from one or more of lithium-rich manganese-based positive electrode materials, nickel-manganese spinel materials, medium-low nickel ternary materials, and lithium cobalt oxide or other ternary materials used under high pressure. The conductive agent can be selected from one or more of conductive carbon black, acetylene black, Ketjen black, and carbon nanofibers. The binder can be selected from one or more of PVDF, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, and styrene-butadiene rubber.

[0063] The more positive electrode lithium replenishing materials there are in the positive electrode active material layer, the better the lithium replenishing effect can be achieved. However, too much lithium replenishing materials will inevitably lead to a decrease in the content of positive electrode active materials, which is not conducive to the improvement of the positive electrode sheet capacity and battery energy density. Based on the above considerations, the mass content of the positive electrode active material in the positive electrode active material layer is controlled to be no less than 94%, and the mass content of the positive electrode lithium replenishing material is 0.3% to 6%.

[0064] The present application does not specifically limit the preparation method of the positive electrode sheet, and the positive electrode sheet can adopt a conventional preparation method in the art. For example, the positive electrode active material, the positive electrode lithium supplement material, the conductive agent and the binder are dispersed in a solvent in proportion to obtain a slurry, and then the slurry is coated on at least one surface of the positive electrode current collector, and the positive electrode sheet can be obtained after drying, slitting and rolling.

[0065] A fourth aspect of the present application provides a lithium-ion battery, comprising the positive electrode sheet provided in the third aspect of the present application.

[0066] Since the lithium-ion battery includes a positive electrode sheet with a lithium-supplementing material having a low activation voltage and high interface stability, it can exert a stable and excellent lithium-supplementing effect under conventional charge and discharge voltages. As a lithium source, it can efficiently delithiate during the first cycle of charging and provide abundant lithium ions to make up for the irreversible lithium ions consumed during the formation of the SEI film, thereby improving the first cycle coulombic efficiency and cycle capacity retention rate of the battery.

[0067] The lithium-ion battery of the present application includes, in addition to a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte.

[0068] Among them, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector. Among them, the negative electrode current collector can be selected from the negative electrode current collectors conventionally used in the art, such as copper foil. The negative electrode active material layer can also refer to the conventional composition in the art, for example, the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder. Among them, the negative electrode active material can be selected from the negative electrode active materials conventionally used in the art, including but not limited to one or more of natural graphite, artificial graphite, silicon-carbon material, silicon-oxygen material, and hard carbon. The composition of the conductive agent and the binder can refer to the types of conductive agents and binders in the positive electrode sheet, which will not be repeated here.

[0069] The present application does not specifically limit the preparation method of the negative electrode sheet, and it can adopt a conventional preparation method in the art. For example, the negative electrode active material, the conductive agent and the binder are dispersed in a solvent in proportion to obtain a slurry, and then the slurry is coated on at least one surface of the positive electrode collector, and the negative electrode sheet can be obtained after drying, slitting and rolling.

[0070] The function of the separator is to separate the positive electrode sheet from the negative electrode sheet and provide a channel for lithium ion migration. The present application does not specifically limit the type of separator, and any separator commonly used in the art, such as a polypropylene separator, a polyethylene separator, etc., can be used.

[0071] The present application does not specifically limit the type of electrolyte, which may be selected from liquid electrolytes, solid electrolytes or gel-type polymer electrolytes commonly used in the art.

[0072] The lithium-ion battery of the present application can be prepared by referring to conventional methods in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence, and then a battery cell is obtained through a lamination or winding process, and then the lithium-ion battery of the present application is obtained through baking, liquid injection, formation, packaging and other processes.

[0073] Hereinafter, the positive electrode lithium supplement material of the present application and its preparation method and application are described in detail through specific embodiments.

[0074] Example 1

[0075] The chemical composition of the positive electrode lithium supplement material in this embodiment is Li 1.95 MnO3, the preparation method thereof comprises the following steps:

[0076] 1) LiOH and MnO2 were mixed in a molar ratio of 1.95:1 to obtain sample P1;

[0077] 2) using a ball mill to finely mix sample P1 at a rotation speed of 400 rpm for 6 hours to obtain sample P2;

[0078] 3) Place sample P2 in a muffle furnace, heat it to 600°C at a heating rate of 5°C / min in an air atmosphere, keep it at that temperature for 4 hours for a sintering, and then cool it naturally to room temperature to obtain sample P3;

[0079] 4) The sample P3 was finely milled using a ball mill at a speed of 600 rpm for 6 hours to obtain a sample P4;

[0080] 5) Place sample P4 in a muffle furnace, heat it to 900°C at a heating rate of 5°C / min in an air atmosphere, keep it at that temperature for 12 hours for secondary sintering, and then cool it naturally to room temperature to obtain sample P5;

[0081] 6) Sample P5 was ball-milled at 800 rpm using a ball mill until the D50 particle size was 0.8 μm to obtain a positive electrode lithium supplement material.

[0082] Example 2

[0083] The chemical composition of the positive electrode lithium supplement material in this embodiment is Li 1.92The preparation method of MnO3 is basically the same as that of Example 1, except that step 1) is to mix LiOH and MnO2 at a molar ratio of 1.92:1. The remaining steps are the same as those of Example 1.

[0084] Example 3

[0085] The chemical composition of the positive electrode lithium supplement material in this embodiment is Li 1.9 Mn 0.95 Co 0.0 5O3, the preparation method thereof is basically the same as that of Example 1, except that step 1) is: mixing LiOH, MnO2, and CoO in a molar ratio of 1.9:0.95:0.05. The remaining steps are the same as those of Example 1.

[0086] Example 4

[0087] The chemical composition of the positive electrode lithium supplement material in this embodiment is Li 1.95 MnO3, the preparation method thereof is basically the same as that in Example 1, except that, step 6) is: ball milling the sample P5 at a speed of 800 rpm using a ball mill until the D50 particle size is 1.5 μm to obtain a positive electrode lithium supplement material.

[0088] Example 5

[0089] The chemical composition of the positive electrode lithium supplement material in this embodiment is Li 1.95 MnO3, its preparation method is basically the same as that in Example 1, except that, step 6) is: ball milling the sample P5 at a speed of 800 rpm using a ball mill to obtain a D50 particle size of 3 μm to obtain a positive electrode lithium supplement material.

[0090] Example 6

[0091] The chemical composition of the positive electrode lithium supplement material in this embodiment is Li 1.9 Mn 0.95 Mg 0.05 O3, the preparation method thereof is basically the same as that of Example 3, except that step 1) is: mixing LiOH, MnO2, and MgO in a molar ratio of 1.9:0.95:0.05. The remaining steps are the same as those of Example 3.

[0092] Example 7

[0093] The chemical composition of the positive electrode lithium supplement material in this embodiment is Li 1.9 Mn 0.95 Mo 0.05 O3, the preparation method thereof is basically the same as that of Example 3, except that step 1) is: LiOH, MnO2, M oO3 was mixed in a molar ratio of 1.9:0.95:0.05. The remaining steps were consistent with Example 3.

[0094] Example 8

[0095] The chemical composition of the positive electrode lithium supplement material in this embodiment is Li 1.9 Mn 0.95 Ni 0.05 O3, the preparation method thereof is basically the same as that of Example 3, except that step 1) is: mixing LiOH, MnO2, and NiO in a molar ratio of 1.9:0.95:0.05. The remaining steps are the same as those of Example 3.

[0096] Comparative Example 1

[0097] The chemical composition of the positive electrode lithium supplement material in this comparative example is Li2MnO3, and its preparation method is basically the same as that in Example 1, except that step 1) is to mix LiOH and MnO2 in a molar ratio of 2:1. The remaining steps are the same as those in Example 1.

[0098] Comparative Example 2

[0099] The chemical composition of the positive electrode lithium supplement material in this comparative example is Li2NiO2, and its preparation method includes the following steps:

[0100] 1) In an inert atmosphere, Li2O and LiOH are mixed at a molar ratio of 1:1 to obtain a lithium source, the lithium source and NiO are mixed at a molar ratio of Li / Ni=2:1 to obtain a mixture, and the mixture is ball-milled at a speed of 800 rpm for 1 h using a ball mill to obtain a mixed powder;

[0101] 2) placing the mixed powder in a muffle furnace, heating the temperature to 500°C at a heating rate of 5°C / min under an inert atmosphere, keeping the temperature for 2 hours, then heating the temperature to 740°C at a heating rate of 5°C / min, keeping the temperature for 12 hours, and then cooling the temperature to room temperature to obtain a sintered material;

[0102] 3) The sintered material was ball-milled at a rotation speed of 1000 rpm in an inert atmosphere until the D50 particle size was 1.5 μm to obtain a positive electrode lithium supplement material.

[0103] Comparative Example 3

[0104] The chemical composition of the positive electrode lithium supplement material in this comparative example is Li5FeO4, and its preparation method includes the following steps:

[0105] 1) In an inert atmosphere, Li2O and LiOH are mixed at a molar ratio of 1:1 to obtain a lithium source, the lithium source and Fe2O3 are mixed at a molar ratio of Li / Fe=5:1 to obtain a mixture, and the mixture is ball-milled at a speed of 800 rpm for 1 h using a ball mill to obtain a mixed powder;

[0106] 2) placing the mixed powder in a muffle furnace, heating the temperature to 500°C at a heating rate of 5°C / min under an inert atmosphere, keeping the temperature for 2 hours, then heating the temperature to 900°C at a heating rate of 5°C / min, keeping the temperature for 6 hours, and then cooling the temperature to room temperature to obtain a sintered material;

[0107] 3) The sintered material was ball-milled at a rotation speed of 1000 rpm in an inert atmosphere until the D50 particle size was 1.5 μm to obtain a positive electrode lithium supplement material.

[0108] Comparative Example 4

[0109] The chemical composition of the positive electrode lithium supplement material of this comparative example is Li 1.7 The preparation method of MnO3 is basically the same as that of Example 1, except that step 1) is to mix LiOH and MnO2 at a molar ratio of 1.7:1. The remaining steps are the same as those of Example 1.

[0110] Comparative Example 5

[0111] The chemical composition of the positive electrode lithium supplement material of this comparative example is Li 1.7 Mn 0.95 Co 0.05 O3, the preparation method thereof is basically the same as that of Example 1, except that step 1) is: mixing LiOH, MnO2, and CoO in a molar ratio of 1.7:0.95:0.05. The remaining steps are the same as those of Example 1.

[0112] Comparative Example 6

[0113] The chemical composition of the positive electrode lithium supplement material in this comparative example is Li 2.0 Mn 0.95 Co 0.05 O3, the preparation method thereof is basically the same as that of Example 1, except that step 1) is: mixing LiOH, MnO2, and CoO in a molar ratio of 2.0:0.95:0.05. The remaining steps are the same as those of Example 1.

[0114] Test Case

[0115] 1. The following performance tests were performed on the positive electrode lithium supplement materials of the above embodiments and comparative examples:

[0116] A. Specific surface area

[0117] Test method: See GB / T 19587-2004 "Determination of specific surface area of ​​solid substances by gas adsorption BET method (GB / T19587-2004)". The test results are shown in Table 1.

[0118] B. SEM test

[0119] Test method: Use scanning electron microscopy to observe the morphology of the positive electrode lithium supplement material. Figure 3 This is a SEM image of the positive electrode lithium supplement material of Example 3, as shown Figure 3 As shown, the positive electrode material is a primary particle without obvious spherical or other secondary particle morphology.

[0120] 2. The positive electrode lithium supplement materials of the above embodiments and comparative examples are respectively made into positive electrode sheets, and then assembled with metal lithium negative electrode, electrolyte and separator according to the following method to obtain button batteries, the method is as follows:

[0121] The positive electrode lithium supplement material, SP and PVDF were mixed in a mass ratio of 80:10:10, and dispersed in NMP solvent to obtain a positive electrode slurry. The slurry was heated at 3 mg / cm 2 The surface density of the electrolyte is coated on an aluminum foil current collector, and the positive electrode sheet is obtained after drying, punching and rolling. The button battery shell, the positive electrode sheet, the PP separator and the metal lithium sheet are stacked in sequence, and the button battery is obtained after the electrolyte is added dropwise.

[0122] The electrolyte includes a solvent and a lithium salt, the solvent is a mixture of EC, DMC and DEC in a volume ratio of 1:1:1, and the lithium salt is LiPF6, and its concentration in the electrolyte is 1.0 mol / L.

[0123] The button cells assembled above were tested for the following properties:

[0124] A. Irreversible capacity of the first cycle

[0125] Test method: At 25°C, charge and discharge the freshly assembled button cell at a charge and discharge rate of 20 mA / g in the cut-off voltage range of 2.5 to 4.8 V, record the first cycle charge capacity C and the first cycle discharge capacity D of the battery, and calculate the first cycle irreversible capacity of the battery by Q1=CD.

[0126] The higher the first-cycle irreversible capacity of the battery, the easier it is to activate the positive electrode lithium replenishment material and the better the lithium replenishment effect.

[0127] B. Air stability

[0128] Test method: Expose the button cell to an environment with a temperature of 25°C and a humidity of 30% for 24 hours, then dry the sample, charge and discharge it at a charge and discharge rate of 20mA / g in the cut-off voltage range of 2.5 to 4.8V, and record the irreversible capacity Q2 of the first cycle of the battery.

[0129] The gram capacity decay rate is calculated by the following formula:

[0130] Gram capacity decay rate = (Q1-Q2) / Q1×100%.

[0131] The smaller the gram capacity decay rate of the sample, the higher the air stability.

[0132] The above test results are shown in Table 1.

[0133] 3. The positive electrode active materials of the above embodiments and comparative examples are respectively made into positive electrode sheets, and then combined with a graphite negative electrode, an electrolyte and a separator to obtain a full battery according to the following method:

[0134] 1) Preparation of positive electrode sheet: Li-rich manganese-based positive electrode material Li 1.1 Ni 0.33 Co 0.05 Mn 0.52 O2, positive electrode lithium supplement material, SP and PVDF were mixed in a mass ratio of 96:0.5:1.5:2 and dispersed in NMP solvent to obtain positive electrode slurry. The slurry was heated at 12 mg / cm 2 The surface density is coated on the aluminum foil current collector, and the positive electrode sheet is obtained after drying, punching and rolling;

[0135] 2) Preparation of negative electrode sheet: artificial graphite, conductive agent SP, and binder CMC were mixed in a mass ratio of 95:2.5:2.5, and dispersed in water to obtain negative electrode slurry. The slurry was heated to 10 mg / cm 2 The surface density of the electrode is coated on the copper foil current collector, and the negative electrode sheet is obtained after drying, punching and rolling.

[0136] 3) Assembly of lithium-ion battery: stack the positive electrode sheet, PP separator and negative electrode sheet in order, wind them to obtain a battery cell, then place the battery cell in an aluminum-plastic film packaging bag, inject electrolyte to seal the bag, and perform electrolyte formation to obtain a lithium-ion battery;

[0137] The electrolyte includes a lithium salt and a solvent, wherein the solvent is a mixture of EC, DMC, DEC, FEC and VC in a volume ratio of 30:30:20:18:2, and the lithium salt is LiPF6, and its concentration is 1.0M LiPF6.

[0138] The following performance tests were performed on the full battery assembled above:

[0139] A. First cycle charging capacity

[0140] Test method: At 25°C, charge and discharge the freshly assembled full battery at a charge and discharge rate of 20mA / g in the cut-off voltage range of 2.5 to 4.8V, and record the battery's first cycle charge capacity in grams.

[0141] B. First-cycle Coulomb efficiency

[0142] Test method: At 25°C, charge and discharge the freshly assembled full battery at a charge and discharge rate of 20mA / g in the cut-off voltage range of 2.5-4.8V, record the battery's first cycle charge capacity C, record the first cycle discharge capacity D, and the first cycle coulombic efficiency η = D / C × 100%.

[0143] C. Capacity retention rate after 100 cycles at 25℃

[0144] Test method: At 25°C, charge and discharge the freshly assembled full battery at a charge and discharge rate of 20mA / g in the cut-off voltage range of 2.5 to 4.8V, record the first cycle discharge capacity D1, record the discharge capacity D2 when the battery is cycled to 100 cycles, and the capacity retention rate after 100 cycles at 25°C is k=D2 / D1×100%.

[0145] The above test results are shown in Table 2.

[0146] Table 1

[0147] Serial number <![CDATA[Specific surface area (m 2 / g)]]> First cycle irreversible capacity (mAh / g) Gram capacity decay rate (%) Example 1 1.37 286.4 0.79 Example 2 1.39 294.5 0.33 Example 3 1.35 308.2 0.56 Example 4 0.76 271.3 0.18 Example 5 0.42 205.4 0.11 Example 6 1.37 298.5 0.80 Example 7 1.36 299.7 0.62 Example 8 1.37 304.2 0.51 Comparative Example 1 1.35 153.9 0.45 Comparative Example 2 0.72 317.6 25.15 Comparative Example 3 0.77 742.4 68.40 Comparative Example 4 1.33 153.8 0.82 Comparative Example 5 1.36 106.5 0.77 Comparative Example 6 1.35 217.1 0.25

[0148] Table 2

[0149]

[0150]

[0151] The following conclusions can be drawn from Table 1 and Table 2:

[0152] 1) From the comparison between Example 1 and Example 2, it can be seen that the degree of non-stoichiometric ratio of Example 2 is increased compared with Example 1, and the lithium vacancy defects are also increased accordingly. From the performance test results, it can be seen that the first-cycle irreversible capacity of Example 2 is improved, which means that the lithium replenishment ability is enhanced; in addition, both Examples 1 and 2 can maintain good air stability, and the gram capacity attenuation rate is less than 1%; at the same time, due to the increase in defect content, the lithium replenisher of Example 2 has better improvements on the full battery charging gram capacity, the first-cycle coulomb efficiency and the capacity retention rate of 100 cycles at 25°C.

[0153] 2) From the comparison between Example 2 and Example 3, it can be seen that Example 3 further increases the concentration of lithium vacancy defects on the basis of Example 2, and introduces heterostructure doping ions to increase the defect content, thereby improving the lithium replenishment ability, while improving the first-cycle charging capacity of the full battery, the first-cycle coulomb efficiency and the capacity retention rate of 100 cycles at 25°C.

[0154] 3) From the comparison of Examples 1, 4, and 5, it can be seen that as the particle size of the positive electrode lithium replenishing material increases, its specific surface area gradually decreases, and accordingly, the irreversible capacity of the first cycle decreases, especially when the particle size D50 of the positive electrode lithium replenishing material is greater than 1.5 μm, the irreversible capacity of the first cycle decays seriously, and the lithium replenishing effect becomes worse; as the specific surface area decreases, the contact area between the positive electrode lithium replenishing material and the air decreases, and its gram capacity decay rate can be further reduced, and the air stability of the material can be further improved. In order to make the positive electrode lithium replenishing material have both excellent air stability and lithium replenishing effect, its particle size should be 0.1 μm to 1.5 μm, more preferably 1.5 μm.

[0155] 4) From the comparison of Examples 3, 6, 7, and 8, it can be seen that, on the basis of having the same non-stoichiometric ratio, the use of different types of doping elements such as Co, Mg, Mo, and Ni to form doping defects can achieve a higher first-cycle irreversible capacity and a lower gram capacity decay rate, showing good lithium replenishment effect and air stability, and the battery's first-cycle charging gram capacity, first-cycle coulomb efficiency, and 100-cycle capacity retention rate at 25°C are also generally excellent.

[0156] 5) From the comparison between Example 1 and Comparative Example 1, it can be seen that the use of non-stoichiometric ratio to construct defects significantly improves the first-cycle irreversible capacity of the battery, improves the lithium replenishment ability of the material, and thus improves the first-cycle charging capacity, first-cycle coulomb efficiency and 25°C cycle performance of the full battery.

[0157] 6) From the comparison between Example 4 and Comparative Examples 2 to 3, it can be seen that the manganese-based lithium replenishing material of the present application has a lower irreversible capacity in the first cycle and a relatively poor lithium replenishing effect compared to lithium replenishing materials such as lithium nickelate and lithium ferrite. However, the gram capacity attenuation rate of Example 4 is significantly lower than that of Comparative Examples 2 and 3, indicating that the manganese-based lithium replenishing material of the present application has better air stability.

[0158] 7) From the comparison between Example 1 and Comparative Example 4, and Example 3 and Comparative Example 5, it can be seen that the non-stoichiometric ratio of the positive electrode lithium supplement material should not be too large. 2-x Mn 1-y M y When x in O3 is greater than 0.2, the material is very likely to generate spinel LiMn2O4 impurity phase, which greatly reduces the irreversible capacity of the first cycle and causes the lithium replenishment effect to deteriorate.

[0159] 8) From the comparison between Example 1 and Comparative Example 1, it can be seen that although the lithium-supplementing material can have excellent air stability only by introducing heterostructure doping ions, the first-cycle irreversible capacity of the material is significantly poor. The reason is that when the lithium content in the material is sufficient and there are no lithium vacancies, the Li2MnO3 material is more likely to form an idealized crystal structure, and the energy barrier for the formation of defect structures is increased, resulting in difficulty in constructing defects even when doping ions are introduced.

[0160] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A positive electrode lithium supplement material, wherein: The positive electrode lithium supplement material is a non-stoichiometric compound, and the chemical composition of the positive electrode lithium supplement material is Li 2-x Mn 1-y M y O3, where M is a doping element, 0<x≤0.2, 0≤y≤0.2; The valence state of M is not +4, or the pure phase lithium oxide of M is isomerized with the layered Li2MnO3 material.

2. The positive electrode lithium supplement material according to claim 1, wherein: M includes one or more of Mg, Al, Ti, V, Cr, Fe, Co, Ni, Zn, Sr, Y, Zr, Nb, Mo, and W.

3. The positive electrode lithium supplement material according to claim 1 or 2, wherein: The positive electrode lithium supplement material is a primary particle.

4. The positive electrode lithium supplement material according to any one of claims 1 to 3, wherein: The D50 particle size of the positive electrode lithium supplement material is 0.1 μm to 2 μm.

5. The positive electrode lithium supplement material according to any one of claims 1 to 4, wherein: The specific surface area of ​​the positive electrode lithium supplement material is 0.5m 2 / g~24m 2 / g.

6. A method for preparing the positive electrode lithium supplement material according to any one of claims 1 to 5, wherein: The preparation method comprises the following steps: 1) mixing a manganese source, a lithium source and a compound containing a doping element M according to a designed ratio to obtain a mixture; 2) Sintering the mixed material to obtain the positive electrode lithium supplement material.

7. The preparation method according to claim 6, wherein: The mixing process is carried out under solid phase conditions.

8. The preparation method according to claim 6 or 7, wherein: The sintering process includes primary sintering and secondary sintering performed sequentially; The primary sintering temperature is 450-600°C and the sintering time is 4-8h; The secondary sintering temperature is 750-950° C., and the sintering time is 6-12 hours.

9. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein: The positive electrode active material layer comprises the positive electrode lithium supplement material according to any one of claims 1 to 5.

10. A lithium ion battery comprising the positive electrode sheet according to claim 9.

Citation Information

Cited By

  • Positive electrode lithium supplement additive and preparation method and application thereof

    CN121394410A